JURIDICAL ANALYSIS OF DECISION NUMBER 27/PDT. G/2019/PN. TBK AGAINST LAWSUITS FOR UNLAWFUL ACTS ON MEANS OF TRANSPORT CONFISCATED BY THE STATE - Ramadhan, Handika; Ansari , Muhammad Insa; Adli , Muhammad (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Article 109 paragraph (2) of Law Number 17 of 2006 concerning Amendments to Law Number 10 of 1995 concerning Customs regulates that means of transport that are solely used to commit criminal acts can be confiscated for the state. Decision Number 102/Pid.Sus/2019/PN.Tbk stated that the means of transporting the MT Yosoa ship were confiscated for the state and in Decision Number 27/Pdt.G/2019/PN.Tbk, the judge ruled that the Tanjung Balai Karimun District Prosecutor's Office Cq. Public Prosecutor had committed an unlawful act. The purpose of the research is to analyze the judge's consideration of the lawsuit for unlawful acts, and the extent of Decision Number 27/PDT. G/2019/PN. Tbk influences the legal interpretation of unlawful acts, as well as the ownership status of MT YOSOA ships that have been decided to be confiscated by the state. This research is a normative juridical research. Data is collected and then analyzed qualitatively. The results of the research show that the judge's decision has weaknesses in legal considerations which results in legal uncertainty and injustice for the parties. In addition, there are inconsistencies in assessing the evidence of ship ownership and elements of unlawful acts, this decision also shows weaknesses in determining liability, due to the lack of parties involved in the lawsuit. It is recommended that the judge be more careful in considering all aspects of the law and exploring the material truth thoroughly. All interested parties must be involved in the lawsuit so that accountability can be clearly established.